2020
DOI: 10.1007/s00122-020-03585-1
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping of spontaneous haploid genome doubling using genotyping-by-sequencing in maize (Zea mays L.)

Abstract: Genome doubling of haploids is one of the major constraints of large-scale doubled haploid (DH) technology. Improving spontaneous haploid genome doubling (SHGD) is an alternative to overcome this limitation. In this study, we aimed to construct a high-density linkage map based on genotyping by sequencing (GBS) of Single Nucleotide Polymorphism (SNPs), to detect QTL and QTL by environment (Q by E) interactions affecting SHGD, and to identify the best trait for mapping and selection of haploid male fertility (HM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…Recently, five inbred lines exhibiting haploid male fertility (HMF) greater than 65% without the use of colchicine were identified by their pollen-shedding ability and proportion of anther emergence [20]. Furthermore, a single large-effect QTL has been identified on chromosome 5 in the inbred that had the highest level of HMF, at 94% [21,22]. Interestingly, this QTL is different from that identified on chromosome 6 within an inbred developed in China that also possesses a high degree of HMF [23].…”
Section: History and Uses Of Dh Technologymentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, five inbred lines exhibiting haploid male fertility (HMF) greater than 65% without the use of colchicine were identified by their pollen-shedding ability and proportion of anther emergence [20]. Furthermore, a single large-effect QTL has been identified on chromosome 5 in the inbred that had the highest level of HMF, at 94% [21,22]. Interestingly, this QTL is different from that identified on chromosome 6 within an inbred developed in China that also possesses a high degree of HMF [23].…”
Section: History and Uses Of Dh Technologymentioning
confidence: 99%
“…Possible candidate genes for large-effect SHGD QTL have been suggested [21,23]. The gene absence of first division (afd1) is characterized by having an absence of first division during meiosis Furthermore, linkage mapping within a bi-parental mapping population using the same high SHGD parent as was used by Ren et al [21] identified a large-effect QTL possessing additive gene action in the same region as qshgd1 ( Figure 2) [22]. Similarly, two small-effect QTL in the same regions as qshgd2 and qshgd3 identified by Ren et al [21] were also detected ( Figure 2) [22].…”
Section: Genetic Architecture and Candidate Genes Of Spontaneous Haplmentioning
confidence: 99%
See 3 more Smart Citations